(untitled) (Fiep Bulletin - online, 2014)
The therapeutic horsebackriding is indicated as therapy in the following cases: motor disorders caused by motoneurons injuries; cerebral injuries; evolutions and behavior disturbs and orthopedics pathologies (FREIRE, 1999). In this context, our objective of the present work was to evaluate the standard of walking and the corporal position, in practitioners of horsebackriding with cerebral paralysis, looking for to relate the walking and position with the practical work developed in the therapeutic horsebackriding Center. Participated on the present study, 32 patients with Cerebral Paralysis, of both the sex. Evaluations had been made daily before and after the therapy, using the scale of measurement of the thick motor function of patients GMFM (Gross Motor Function Measure), with 88 separate items in 5 dimensions. The instrument used for analyzes statistics was the SPSS13.0, with statistics of pair upped the sample (p<0,05). The results had been: in the dimension A-To lie down and to roll, the patients had gotten a significant improvement (average difference=-3,3756). In dimension B-To seat, the patients had had a satisfactory improvement (average difference=-6,9791). Once the time that found difficulties in this dimension. In dimension C-Kneeling, children had gotten with the treatment a significant improvement (average difference=-2,5301). In dimension D-To be on both Foots, the patients had presented satisfactory motor evolution (average difference=-3,3664). In the dimension E-To walk/To run/To jump the patients they had gotten greater functional profit, in relation its motor independence (average difference=-2,1724).We concludes that the results had pointed a respect increase in the averages of all of evaluated motor structures in the standard of march and the corporal position.